Effect of intramuscular midazolam premedication on patient satisfaction in women undergoing general anaesthesia: a randomised control trial. Issue 6 (22nd June 2022) - Song, Seung Woo; Jin, Younghyun; Lim, Hyunjae; Lee, Jonghoon; Lee, Kwang Ho
Abstract : Objective: To determine the effect of premedication with intramuscular midazolam on patient satisfaction in women undergoing general anaesthesia. Trial design, setting and participants: Double-blind, parallel randomised control trial at a tertiary care medical centre in South Korea. Initially, 140 women aged 20–65 years who underwent general anaesthesia and had an American Society of Anesthesiology physical status classification of I or II were randomly assigned to the intervention group or the control group, and 134 patients (intervention n=65; control n=69) completed the study. Intervention: Intramuscular administration of midazolam (0.05 mg/kg) or placebo (normal saline 0.01 mL/kg) on arrival at the preoperative holding area. Main outcomes: The primary outcome was the patient's overall satisfaction with the anaesthesia experience as determined by questionnaire responses on the day after surgery. Satisfaction was defined as a response of 3 or 4 on a five-point scale (0–4). The secondary outcomes included blood pressure, heart rate, oxygen desaturation, recovery duration and postoperative pain. Results: Patients who received midazolam were more satisfied than those who received placebo (percentage difference: 21.0%, OR 3.56, 95% CI 1.46 to 8.70). A subgroup analysis revealed that this difference was greater in patients with anxiety, defined as those whose Amsterdam Preoperative Anxiety and Information Scale anxiety score was ≥11, than that for the whole sample population (percentage difference: 24.0%, OR 4.33, 95% CI 1.25 to 14.96). Both groups had similar heart rates, blood pressure and oxygen desaturation. Conclusion: Intramuscular administration of midazolam in women before general anaesthesia in the preoperative holding area improved self-reported satisfaction with the anaesthesia experience, with an acceptable safety profile. Trial registration number: KCT0006002.